The Definitive Guide to Java Swing (Third Edition) - Zukowski, John (Apress, 2013)
This book can be read from cover to cover, but it doesn’t have to be done that way. It’s true that later sections of the book assume you’ve absorbed knowledge from the earlier sections. However, if you want to find something on a topic covered in a later chapter, you don’t need to read all the chapters that precede it first. If you come across something that’s unfamiliar to you, you can always go back to the earlier chapter or search the index to locate the information you need.